Le puits de ténèbres — Rencontre avec Guillaume Séverac-Schmitz, metteur en scène, et Clément Camar-Mercier, traducteur et dramaturge, autour de La Duchesse d’Amalfi (Création, Cratère Scène nationale, Alès, janvier 2019) - Line Cottegnies; Guillaume Séverac-Schmitz; Clément Camar-Mercier (Sillages Critiques)
A Conversation between Line Cottegnies, Guillaume Séverac-Schmitz, director and head of the company Eudaimonia, and Clément Camar-Mercier, translator and dramaturg, about the production of The Duchess of Malfi, which opens at the Cratère Scène nationale (Alès) in January 2019. The interviews were conducted on 14 and 15 November 2018 in Paris.